Optical determination of carbon dioxide and oxygen by a fluorescent membrane to evaluate the freshness of meat products. Issue 6 (2nd November 2019) - Anusankari, S.; Balaji Ganesh, A.; Subasri, R.; Deepa, N.
Abstract: The present study proposes the design of a portable noninvasive optical sensor consisting of fluorescence-based sensing membrane for the purpose of evaluating the freshness of various consumable meats by measuring the dual parameters of oxygen and carbon dioxide. The sensor film is attached to the inner wall of an air-tight container integrated with opto-electronics circuits. The performance characteristics of the sensor, such as the photo-stability, response time, and cross-sensitivity, were characterized to demonstrate the effectiveness of sensing before testing actual samples. The fluorescent sensor reacts rapidly with an increase in CO2 ranging from 700 to 3800 ppm and a decrease of oxygen between 7.5 and 7 ppm observed in a period of 8 h. The sensor shows the maximum and minimum relative error of +3.80% and –2.24% for CO2 and +2.39% and –4.34% for O2, respectively. The accuracy of the developed sensor was ±1.75% with high precision of 5000 ± 28.2 and 7 ± 0.04 ppm for CO2 and O2, respectively, which implies low standard deviation values. The results were comparable with a reference instrument. This simple, yet nondestructive and inexpensive system analyzes the quality of meat at domiciliary levels.